Mugged : racial demagoguery from the seventies to Obama - Coulter, Ann H. frey50 (New York : Sentinel, 2012)
Ann Coulter fearlessly explains the real history of race relations in this country, including how white liberals twist that history to spring the guilty, accuse the innocent, and engender racial hatreds, all in order to win politically.
Race wars of convenience, not necessity -- Innocent until proven white -- Guilty until proven black -- Hey, whatever happened to that story... -- That old black magic -- People in doorman buildings shouldn't throw stones -- Liberal-black relations: their landlord and their friend -- Rodney King: the most destructive edit in history -- Trial of the century: Mark Fuhrman's felony conviction -- Post-OJ verdict: paradise -- Liberals are the new blacks -- Civil rights chickenhawks -- You racist! -- Dreams of my assassination -- Obama, race demagogue -- The media cry "racist" in a crowded theater -- White guilt kills.
Keywords: Race -- Political aspects -- United States; United States -- Race relations -- Political aspects; United States -- Politics and government -- 20th century; United States -- Politics and government -- 21st century